A new species of Hypoaspis Canestrini (Acari: Laelapidae) associated with the Hercules beetle (Coleoptera: Scarabaeidae) in China - Xu, Jing-Xiang; Song, Xia-Qing; Lu, Wen-Zhi; Xie, Li-Xia; Yan, Yi (Zootaxa, 2026)
A new species of the genus Hypoaspis Canestrini, 1885, Hypoaspis lisongorum sp. nov., is described and illustrated on the basis of the female and male, collected from a larva of Dynastes hercules hercules (Coleoptera: Scarabaeidae) in China.